Studytok as A Tool for Promoting Media Literacy : Insight From University Students - Julynar Putri Ayu Sitorus; Putri Salsabila Arsitha Fitri; Rita Hartati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study explores the effectiveness of StudyTok, a TikTok-based educational initiative, in fostering media literacy among university students. Using a descriptive quantitative approach, data were gathered from 40 students to evaluate the platform's impact on engagement, reading comprehension, writing proficiency, and critical thinking. Results revealed that 85% of participants found StudyTok engaging, with notable improvements in reading comprehension (70%) and critical thinking (75%). However, only 60% reported significant enhancement in writing skills, indicating room for more structured content in this area. The study highlights generational differences in platform navigation, with digital natives adapting seamlessly compared to digital immigrants who faced initial challenges. Guided by Potter’s Media Literacy Theory, this research underscores StudyTok’s potential to bridge digital literacy gaps and recommends its integration into educational curricula to foster inclusive, critical media consumption skills.